Effects of Psychoeducational Group on Muslim Spouses’ Communication (Jurnal Pembangunan Sosial, 2017)
Statistics released by Jabatan Kemajuan Islam Malaysia (JAKIM) shows that the marital conflict and divorce rates among Muslim increases every year. There are a range of factors associated with marital conflict and divorce. In present study communication is highlighted as the factor that contribute to marital conflict and divorce among Muslim spouses. In an effort to help spouses manage and overcome marital conflicts, Muslim spouses need for an Islamic base according to the religious perspective. For that purposes this article is an attempt to examine the effects of psychoeducational group known as Marital Psycho-Spiritual Intervention (MP-SI) on communication among Muslim husbands and wives at Felda in Kedah. A psychoeducational group is a systematic effort to help improve the functioning of Muslim spouses’ communication through education and preventative means which widely used in guidance and counseling services. It is a group approach conducted by marriage counselors to educate and disseminating knowledge and skills related to marriage relationships. The randomized controlled trials (randomized control group design with pretest, posttest and follow up test) was used in this study. The experimental and control group of this study was totally composed of 76 participants, 38 in experimental group and 38 in control group. Participants in experimental group received a treatment of MP-SI for 6 weeks (2 hours per week). Marital Communication Inventory (MCI) was utilized to obtain the data for communication in three times (pretest, posttest, and follow up). A Mixed Between-Within Subjects ANOVA was used to see the differences between the mean scores of pretest, posttest, and follow up test within both experimental and control group. The results from mixed between-within subjects ANOVA showed that there were a statistically significant main effect of time and group for communication. Participants in the experimental group showed improvement in communication compared to the control group over the three time periods. These findings demonstrated the MP-SI conducted in this study had a higher impact on the experimental group and the effect was similar on the male and female participants. These results reveal valuable information that an Islamic psycho-spiritual approach that emphasizes the spiritual practices and element of nafs (soul), aql (intellect), qalb (heart), and ruh (spirit) help improve Muslim spouses’ communication.